The Relationship between The Level of Side Effects of ARV Drugs in ODHA Patients to The Level of The Compliance Use of ARV Drugs - Aisha Maulidya Sari (Pharmaceutical Journal of Indonesia, 2021)
HIV or  Human Immunodeficiency Virus  is one of the causes of AIDS ( Acquired Immunodeficiency Syndrome)  that is a disease that attacks the body's immunity. One therapy for treating HIV/AIDS is with antiretroviral therapy. In antiretroviral therapy high adherence is needed at least 95% of the dose should not be forgotten to achieve desired virological suppression. One factor affecting compliance is the side effects of ARV drugs that appear in ODHA patients undergoing antiretroviral therapy.  This study aims at knowing the relationship of the level of drug side effects to the level of compliance in the treatment of ARVs in ODHA patients.  This research uses  cross-sectional  in ODHA patients in Puskesmas Dinoyo, Malang City.   The results of the study were found that the level of ODHA patient drug side effects at the Puskesmas Dinoyo VCT Clinic, the ODHA patient who did not experience side effects, was 5.8% , side effects a little 21.3%, moderate side effects 21.2% and high side effects 51.8%. Compliance with taking ODHA patient medication at the VCT Clinic Puskesmas Dinoyo patients with low adherence of 1.2%, moderate compliance 69.4% and high compliance 29.4%.  There is no significant relationship between the level of side effects of ARV drugs in ODHA patients with the level of compliance with ARV drug use with values  p- the value obtained is 0.412.